Frequency and Prognostic Value of IDH Mutations in Korean Patients With Cholangiocarcinoma - Kim, Nah Ihm; Noh, Myung-Giun; Kim, Jo-Heon; Won, Eun Jeong; Lee, Yu Jeong; Hur, Younghoe; Moon, Kyung-Sub; Lee, Kyung-Hwa; Lee, Jae-Hyuk (Frontiers in Oncology, 2020)
The molecular profile of cholangiocarcinoma (CC) remains elusive. The prognostic value of isocitrate dehydrogenase (IDH) mutations in CC is controversial, and there have been few relevant studies in Asian populations. In the present study, we investigated the frequency and prognostic significance of IDH mutations in Korean patients with CC. CC specimens were collected from patients who underwent surgical liver resection between 2004 and 2019. Clinical and pathological data were retrospectively reviewed from medical records. Mutational IDH profiling was performed by peptide nucleic acid-mediated PCR clamping in 206 surgical specimens; IDH-mutant samples were confirmed by next-generation sequencing (NGS). Of the 195 patients with CC, six (3.13%) were found to exhibit IDH1 (n = 5) or IDH2 (n = 1) mutations. Among patients with IDH1 mutations, four had R132C (c.394C>T) and one had R132G (c.394C>G) mutations. One patient had R172W (c.514A>T) mutations in IDH2. All IDH-mutant samples were of intrahepatic origin, and patients with IDH mutations had physiological to low serum levels of carbohydrate antigen 19-9 (CA19-9). No association between IDH mutation status and long-term survival outcomes was observed. The frequency of IDH mutations was considerably lower than the 10-20% reported in previous studies. The frequency and pattern of IDH mutations in CC are likely to vary among patients with different ethnicities. These findings suggest that characterization of the oncogenic mutation profile in different populations is of high clinical importance.